A Computer Modeling of Fracture Based Pull-Out of Nylon 600 Embedded in Cementitious Matrix - Rr. M.I. Retno Susilorini (Institute of Research and Community Outreach - Petra Christian University, 2009)
This paper reports the development of a computer model that represents a pull-out process of nylon 600 embedded in cementitious matrix. The model is based on fracture approach considering the Poisson’s effect and stable crack length. To back up the model four pull out tests of nylon 600 fiber, diameter 1.1 mm, with two fiber embedment lengths, 100 mm and 120 mm are done. The numerical approach is then compared to the experimental results. The computer model is built on Delphi 7 and named “Program Cabut-Serat Fraktur